2021
DOI: 10.1007/s13555-021-00508-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Alopecia Areata Patient Priority Outcomes Instrument: A Qualitative Study

Abstract: Introduction: Although alopecia areata (AA) profoundly impacts patients' physical appearance, emotional state, and daily activities, no treatment approved for AA currently exists. Patient-reported outcome (PRO) instruments currently used to capture patients' AA experiences do not meet the requirements to support claims of treatment benefit as described in the US Food and Drug Administration's 2009 PRO guidance. Our objective was to explore the consequences and priority treatment outcomes among individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Although the CFA results provided support for consideration of an overall hair loss subscale (Items 1-4), patients with AA present clinically with hair loss on the scalp and/or any hair-bearing area on the body [38]. Moreover, the qualitative evidence obtained during the AAPPO development process demonstrated that not all patients experienced hair loss in each measured location (i.e., scalp, eyebrows, eyelashes, and the body) or prioritized hair loss from each area equally [7]. Therefore, the decision was made to score the four individual Hair Loss items separately and not as a four-item summed domain score.…”
Section: Exploratory and Confirmatory Factor Analysesmentioning
confidence: 98%
See 4 more Smart Citations
“…Although the CFA results provided support for consideration of an overall hair loss subscale (Items 1-4), patients with AA present clinically with hair loss on the scalp and/or any hair-bearing area on the body [38]. Moreover, the qualitative evidence obtained during the AAPPO development process demonstrated that not all patients experienced hair loss in each measured location (i.e., scalp, eyebrows, eyelashes, and the body) or prioritized hair loss from each area equally [7]. Therefore, the decision was made to score the four individual Hair Loss items separately and not as a four-item summed domain score.…”
Section: Exploratory and Confirmatory Factor Analysesmentioning
confidence: 98%
“…AAPPO The 11-item AAPPO [7] contains four items, categorized as ''Hair Loss'' from (1) the scalp, (2) eyebrows, (3) eyelashes, and (4) body, and asks the patient to describe the current amount of hair loss using a five-point response scale that ranges from 0 (no hair loss) to 4 (complete hair loss: ''I do not have any hair on my [insert hair loss area]''). The remaining seven items ask the patient to rate Emotional Symptoms (4 items) and Activity Limitations (3 items) of AA over the past week on a 5-point scale ranging from ''Never'' to ''Always.''…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
See 3 more Smart Citations